Tinjauan Sosiologi Sastra Karya Taufiq Ismail dalam Puisi: Syair Orang Lapar - Falah Arifbilah Subagiyo; Akhmad Fatoni (STIKes Ibnu Sina Ajibarang, 2025)
Literary work always contains the author's view of reality as a social institution created by an author. Issues that are often strung together become a view or criticism of life. It certainly describes social life as a reality that occurs in an environment. One type of literary work that contains a view of reality is his poem Taufiq Ismail entitled